2004
DOI: 10.1074/jbc.m313204200
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor (CCN2) Induces Adhesion of Rat Activated Hepatic Stellate Cells by Binding of Its C-terminal Domain to Integrin αvβ3 and Heparan Sulfate Proteoglycan

Abstract: Connective tissue growth factor (CCN2, also known as CTGF) is a matricellular protein that appears to play an important role in hepatic stellate cell (HSC)-mediated fibrogenesis. After signal peptide cleavage, the fulllength CCN2 molecule comprises four structural modules (CCN2 1-4 ) and is susceptible to proteolysis by HSC yielding isoforms comprising essentially modules 3 and 4 (CCN2 3-4 ) or module 4 alone (CCN2 4 ). In this study we show that rat activated HSC are capable of adhesion to all three CCN2 isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
233
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 56 publications
7
233
0
Order By: Relevance
“…Previous studies have suggested the implications of CTGF in the pathogenesis of hepatic fibrosis characterized by deposition of fibrillar collagens in the liver 21, 44, 45, 46. The full‐length CTGF molecule comprises four structural domains, that is modules 1–4, which are susceptible to proteolysis by hepatic stellate cells, yielding C‐terminal fragments composed of the modules 3 and 4 or the module 4 alone 46.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the implications of CTGF in the pathogenesis of hepatic fibrosis characterized by deposition of fibrillar collagens in the liver 21, 44, 45, 46. The full‐length CTGF molecule comprises four structural domains, that is modules 1–4, which are susceptible to proteolysis by hepatic stellate cells, yielding C‐terminal fragments composed of the modules 3 and 4 or the module 4 alone 46.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have also found that CTGFinduced lung pathology is associated with activation of β-catenin signaling, whereas treatment with CTGF antibody inhibits hyperoxia-activated β-catenin signaling. It is known that CTGF can activate β-catenin signaling by binding to cell surface integrins and lipoprotein receptor-related protein (LRP) 5/6, coreceptors of wingless/Int (Wnt) (13)(14)(15)(16). It is unknown, however, whether activation of β-catenin signaling mediates CTGF-induced alveolar and vascular pathology in neonatal mice.…”
Section: Introductionmentioning
confidence: 98%
“…The transcription complex formed by β-catenin and its DNA-binding partners known as LEF/TCF is able to promote chromatin remodeling and transcriptional initiation in a cell type-specific and context-specific manner, thus playing a key role in embryonic development, cell proliferation, differentiation, and survival. CTGF can directly bind to cell surface integrin complexes thus activating ILK signaling (13,14). CTGF can also directly bind to LRP5/6, coreceptors of Wnt (15,16).…”
Section: Ctgf β-Catenin and Neonatal Lungmentioning
confidence: 99%
“…The activation of the liver stellate cells has been associated with regulation by the integrin family of proteins (8) (9) , and some of these are expressed on hepatic stellate cells (6) (7) .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Similarly, the expression of some integrins, which are present in a variety of cell types, including platelets (5) and liver stellate cells (6) (7) , has been associated with the development of fi brosis (8) (9) . The integrins that are present on platelet membranes express different types of antigens, and, of these, the human platelet antigens (HPA) have received considerable attention (10) .…”
mentioning
confidence: 99%